Kepemimpinan yang Melayani Menghadapi Tantangan dan Manfaat dalam Era Bisnis yang Berkembang - Maudina Alia; Putri Meliana Santoso; Iwanussoleh Iwanussoleh; Mochammad Isa Anshori (Jurnal Riset dan Inovasi Manajemen, 2023)
This article examines servant leadership as a promising approach to addressing challenges in the ever-evolving era of business and organizations. Servant leadership places the interests of and service to subordinates as top priority with the aim of helping them achieve their full potential. In this article, we explore the results and discussion of literature studies on servant leadership, including its influence on organizational performance, creating a harmonious work environment, and building subordinate loyalty. We also identify challenges in practicing servant leadership and provide recommendations for addressing these challenges. This article aims to provide a comprehensive and detailed insight into the importance and benefits of servant leadership in this dynamic era.